Optimizing the potential of Karangtengah village through educational parks and Cananga herbal cafe - Amelia Sholu Pratiwi; Aji Tetuko; Fatimah Nur Azizah; Ni Putu Dea Anantarini (Community Empowerment, 2023)
Karangtengah Village, one of the villages in Bantul Regency, has a rich potential for biodiversity, particularly for family medicinal plants. However, there are still a lot of undeveloped lands that could be better utilized. This program aims to increase community independence in terms of supporting families by encouraging land use or vacant yard optimization. The Karangtengah Village Farmer's Group and PKK women were the targets of this program. The team will transform a plot of land in Karangtengah Village into an educational park and herbal cafe called "Cananga" through this program. The activity starts with the maintenance phase, followed by outreach, TOGA cadre selection, training, mentoring, and the creation of an educational park and herbal cafe. The TOGA conservation cadres received training in the production of high-value functional foods or home-scale industrial-scale herbal medicines as well as a guidebook on the different types of medicinal plants. The stand for the Education Park and Cananga Herbal Cafe was the program's final product. The community receives and experiences the advantages of TOGA, including improved welfare and independent, low-cost health maintenance. In addition, Karangtengah Village can be utilised as a tourist destination with significant educational value.